Association between serum level of advanced glycation end products and obstructive sleep apnea–hypopnea syndrome: a meta-analysis. Issue 11 (November 2018) - Wu, Xingyu; She, Wensheng; Niu, Xun; Chen, Xiong
Objective: This meta-analysis was performed to assess the difference in the serum level of advanced glycation end products (AGEs) between patients with obstructive sleep apnea–hypopnea syndrome (OSAHS) and controls. Methods: A systematic literature search was performed using PubMed, Elsevier, SCI, Wanfang, Weipu, and China National Knowledge Internet. Eligible studies that reported the serum AGE level in patients with OSAHS were identified by two reviewers. Review Manager version 5.2 (The Nordic Cochrane Centre, The Cochrane Collaboration, Copenhagen, Denmark) and R version 3.10 (www.r-project.org ) were employed for data synthesis. Results: Five studies involving 670 subjects were identified. The meta-analysis showed that the mean serum AGE level in the OSAHS group was 0.98 mmol/L higher than those in the control group (95% confidence interval, 0.69–1.27). Conclusions: This meta-analysis showed that the serum AGE level was elevated in patients with OSAHS. This finding suggests that AGEs may play an important role in insulin resistance in OSAHS and serve as a biomarker for patients with OSAHS with a high risk of type 2 diabetes mellitus.